PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA RESTORAN PIZZA HUT DI BANJARMASIN - Susiladewi Susiladewi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2020)
This study aims to determine, (1) the influence between the quality of service provided by Pizza Hut Banjarmasin on Consumer satisfaction, both partially and simultaneously (2) Which service quality dimension is the most dominant influence on consumer satisfaction of Pizza Hut Banjarmasin. The object of this research is the Pizza Hut Restaurant in Banjarmasin with 100 respondents determined by random sampling. The method used in this research is quantitative research which is a research model that requires the calculation of numbers, while the approach used is a survey approach that is research that takes samples from the population and uses a questionnaire as a primary data collection tool. The results of this study indicate that, the quality of Pizza Hut Banjarmasin according to customer perception is good, the level of customer satisfaction for all services provided by Pizza Hut Banjarmasin, namely in general they feel satisfied, as many as 54% who rate good, Neutral 18% while those who answered very satisfied were 16%, and those who said they were not satisfied were 9% and respondents who answered very dissatisfied were 3%. as well as the results of statistical data processing can be seen that there is a significant and direct effect between the quality of Pizza Hut Banjarmasin services consisting of Tangibles, Reliability, Responsiveness, Assurance and Empathy, on customer satisfaction of Pizza Hut Banjarmasin with a regression equation Y = -0.231 + 0.768 X1 + (-0,972) X2 + 0,354 X3 + 0,437 X4 + 0,355 X5 + e and the service quality variable that has the biggest influence on customer satisfaction is the Tangibles variable.